The Andean Pilgrimage - Sallnow, Michael J. (1974)
In the months that go from June to October, thousands of peasants from the mountains of southern Peru undertake the paths that take them on pilgrimage to one or another sanctuary. "Traditional religiosity is an itinerant religiosity" writes Marzal (1971: 225). The main pilgrimage centers are well known: Señor de Qoyllur Rit'ti; the sanctuary of the Lord of Huanca, the Virgin of Copacabana, etc.